Engineering Management: A Comprehensive Review of Challenges, Trends, and Best Practices - Htet , Arkar; Liana, Sui Reng; Aung, Theingi; Bhaumik, Amiya (EDUPEDIA Publisher, 2023)
Abstract: Engineering management is a multidisciplinary field that combines technical knowledge with management skills, aiming to efficiently develop and execute engineering projects. The increasing complexity of modern projects and the dynamic environment in which they are executed have led to the development of various tools, methodologies, and best practices to improve project outcomes. This paper reviews the literature on engineering management, discussing its challenges, emerging trends, and best practices. The findings reveal that effective engineering management is crucial for achieving project success and that organizations must adapt to the rapidly changing landscape.